Sensorimotor perturbation-induced cortical responses by a novel PES system: analysis of the N1 component in healthy adults and Parkinson's disease - Rathke, Christian L.; Pimentel, Victor C. A.; do Espirito-Santo, Caroline Cunha; Vasiljevic, Gabriel A. M.; Dantas, André Felipe Oliveira de Azevedo (Frontiers in Human Neuroscience, 2025)
Perturbation-evoked potentials (PEPs) have been widely used to investigate static and dynamic perturbations on postural and motor control through analysis of cortical responses. In this pilot study, we present an innovative approach using IoT-based Perturbatory Electrical Stimulation (PES) during treadmill walking to assess cortical responses in healthy adults (N = 6) and individuals with Parkinson's disease (N = 4), with a focus on the N1 component. This approach integrates PES and EEG systems through an Internet of Things (IoT) framework utilizing the MQTT protocol, enabling synchronized and wireless data acquisition during gait. The results indicated significant differences in N1 latency (p = 0.005), with the Parkinson's disease group presenting higher latencies in the N1 component (252.50 ± 32.62 ms) compared to the healthy adult group (175.50 ± 30.42 ms). Significant correlations were observed between N1 amplitude and participants' age (r = 0.669, p = 0.049) and between TUG performance and PES intensity (mA) (r = -0.697, p = 0.037). No significant correlations were found between N1 latency and PES intensity (mA), visible motor threshold (mA), or Epworth Sleepiness Scale. These findings contribute to a better understanding of how Parkinson's disease impacts cortical responses to sensorimotor perturbations during gait, particularly regarding sensory processing and motor feedback, and highlight the potential utility of the PES system in future studies in motor control.